PD Lab - Marcel Bilow; Bram Entrop; Jos Lichtenberg; Pieter Stoutjesdijk (Spool, 2015)
PD Lab explores the applications of building sector related product development.  PD lab investigates and tests digital production technologies like CNC milled wood connections. It will also act as a platform in its wider meaning to investigate the effects and influences of file to factory production, to explore the potential in the field of sustainability, material use, logistics and the interaction of stakeholders within the chain of the building process.